NETWORKING DALAM PROGRAM PELAYANAN TRANSPORTASI BATIK SOLO TRANS DI KOTA SURAKARTA - Desi Indah Pratiwi; Priyatno Harsasto; Nunik Retno Herawati (Journal of Politic and Government Studies, 2015)
One of the types of public services offered by the Local Government of Surakarta since 2010 is public transportation service of Batik Solo Trans (BST). However, until now Batik Solo Trans is consideredyet been able to attract people's interest to move using public transportation. It is characterized by the increase number of private vehicles in Surakarta. Therefore, management of Batik Solo Trans needs a network in which there are some actors or stakeholders involved and having different resources and respective role to side by side improve Batik Solo Trans’s service quality. This research has a purpose to understand and explain the partnership between the Local Government of Surakarta with some other actors involved in Batik Solo Trans’s service network in order to improve the quality of public transportation in Surakarta. The research is conducted in Surakarta. The type of research is descriptive qualitative with officials informantof Department of Transportation, Communications and Informatics, Surakarta’s Regional House of Representatives member, operators of Batik Solo Trans, NGOs, entrepreneurs of city bus, andthe general public who useor don’t use the service of Batik Solo Trans. The technique of determining the informantuses purposive sampling technique. The method of collecting data in this research is non participatory observation, in-depth interviews, and literature review. The analysis of datais donethrough interactive model, whereas the validity of data is done throughdata triangulation. Based on the results, the networking in the service of Batik Solo Trans in Surakarta is well-executed butthere are still some barriers or obstacles occurs,that is the different of perception between the actors involved so that the impact leads to the service of Batik Solo Trans which then be less maximal.Suggestions for the Local Government of Surakarta are improving service management of Batik Solo Trans, establishing good communication with stakeholders, and providing sanctions firmly against operators of Batik Solo Trans who violate the Minimum Procedure Standards (SPM). Keywords: Networking, The actors involved, Batik Solo Trans service.